Pelatihan Penyusunan Proposal dan Analisis Biaya-Manfaat dalam Mendukung Pariwisata Olahraga di Dusun Gunung Ambawang - Mustafa, Bob; Zawitri, Sari; Ardhi, Qisthi; Perdhiansyah, Perdhiansyah; Noor, Uray M.; Irawati, Rika (Politeknik Negeri Pontianak, 2022)
One of the government's efforts to achieve tourism development goals is through the development of tourist villages. Deras is one of the villages designated as a strategic tourism area, which was officially designated as a tourist village on April 10, 2021. The purpose of this activity is to increase understanding of tourism object managers and Tourism Awareness Groups (Pokdarwis) in preparing proposals and assessing program implementation and development of new tourist objects through a cost-benefit analysis approach. The training, which was attended by 15 participants, was held on Saturday, August 7, 2021, at Taman Wisata Alam Indah Lestari, which is located at Gunung Ambawang Hamlet, Sungai Deras Village, Kec. Pakedai Bay. All participants enthusiastically participated in this activity and their understanding increased significantly after attending the training. The results of mentoring participants showed that as much as 80% of participants were able to develop activity proposals and conduct cost-benefit analysis for the opening of new tourist objects. It can be said that in general this training activity ran smoothly and was able to increase participants' understanding in preparing activity proposals and applying cost and benefit analysis techniques for opening new tourist attractions.